Evaluating the Feasibility and Acceptability of a Community-Based, Co-Created Yoga Program for Women with Gynecologic Cancer: A Series N-of-1 Feasibility Study - Jenson Price; Brooklyn Westlake; Jennifer Brunet (Current Oncology)
Purpose: Current yoga programs for cancer survivors do not meet participants’ needs and are rarely implemented in community-based settings, despite reported benefits. The aim of the current study was to implement a co-created 12-week bi-modal Hatha-based yoga program for adults diagnosed with gynecologic cancer in the community and assess the feasibility and acceptability of the program and study methods. Methods: Using a mixed methods series N-of-1 A1BA2 research design, participants were recruited from The Ottawa Hospital. Participants self-selected a morning or evening program, completed surveys 9 to 11 times and were interviewed post-program. The yoga instructor was interviewed post-program about her experience delivering the program. Quantitative feasibility outcomes were tracked throughout the study. Qualitative acceptability outcomes were explored during post-program semi-structured interviews. Audio and video recordings of the yoga classes and data from the instructor interview were used to assess fidelity outcomes to determine whether the protocol could be adhered to consistently. Results: Forty-one individuals were screened for eligibility and 20 consented (48.7%). Seventeen participants (85.0%) completed the final survey. Participants attended 83.1% (19.9/24) of classes with varied engagement with optional features. The instructor was 61.3% adherent to the prescribed protocol, using recommended behaviors 44.6% of the time. Participants shared barriers and facilitators that influenced the success of the trial methods and program. Conclusions: The program was well-received and trial methods were moderately successful, but refinements are warranted before a large-scale trial. Community-based yoga programs could be feasible and acceptable for women with gynecologic cancer.